Exploring Safe Sleep and SIDS Risk Perception in an African‐American Community: Focused Ethnography. Issue 3 (7th October 2015) - Zoucha, Rick; Walters, Cynthia A.; Colbert, Alison M.; Carlins, Eileen; Smith, Eileen
Abstract: Objectives: Explore the cultural influences of safe sleep practices by African‐American caregivers of children under 2 years old. Explore the role of health care professionals in promoting safe sleep. Design and Sample: A focused ethnography was used to understand the contextual cultural meaning and experiences of safe sleep practices of African‐American caregivers of children under 2 years. Nineteen African‐Americans participated in this study. Measures: Demographic data were collected and semi‐structured interviews were conducted with individuals and small groups. Saturation of the data occurred after 17 interviews. Data were analyzed using Leininger's four Phases of qualitative data analysis. Results: (Themes): (1) The informants expressed both accurate and inaccurate knowledge of Sudden Infant Death Syndrome (SIDS) and safe sleep practices influenced by personal experiences, hospital education, family, extended family and television; (2) Sleeping with infants and children was viewed as a cultural caring behavior promoting comfort, closeness and protection for infants, children, parents and caregivers; (3) The informants want and are seeking collaboration with nurses and health care professionals who are viewed as important in promoting accurate information about SIDS and safe sleep practices. Conclusion: The role of the nurse can impact accurate outcomes about SIDS and safe sleep practices.